Bronfenbrenner's Bioecological Theory: School Readiness for Children in the Context of Distance Learning During the Covid-19 Pandemic - Bratanoto, Virgilia Zephanya; Latiana, Lita; Forman, Ali; Pranoto, Yuli Kurniawati Sugiyo (Program Studi Magister Pendidikan Anak Usia Dini, 2022)
School readiness is an important factor that affects the child’s development. However, promoting children’s school readiness becomes even more challenging during the COVID-19 pandemic. There is a gap between the implementation of Distance Learning and the limited understanding about effect of Distance Learning to promote children’s school readiness. This study aims to find out how distance learning affects children's school readiness during the Covid-19 pandemic and to understand the role of the children’s environment in promoting children’s school readiness, in terms of Bronfenbrenner's Bio-ecological theory. This research uses a descriptive quantitative method. Data was collected by an online survey. There were 326 parents and 34 KG-B teachers from 16 private schools in Semarang who participated in this study. Data analysis uses descriptive analysis techniques and independent sample t-test. The result finds out that distance learning is less effective in promoting children's school readiness, especially in socio-emotional skills. The role of the ecological system also influences distance learning in promoting school readiness, so for promoting school readiness, both children’s skills and the roles of systems should be emphasized. The findings suggest the school needs to evaluate and review every strategy, planning and implementation of distance learning in their schools. The findings also suggest the kindergarten teachers need to enrich their competence in designing innovative, creative, and interesting distance learning activities, based on digital technology. Keywords: early childhood, school readiness; distance learning References: Agustin, M., Puspita, R. D., Nurinten, D., & Nafiqoh, H. (2020). Tipikal Kendala Guru PAUD dalam Mengajar pada Masa Pandemi Covid 19 dan Implikasinya. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(1). https://doi.org/10.31004/obsesi.v5i1.598 Ayudia, R., Febrialismanto, F., & Solfiah, Y. (2020). Persepsi Orangtua Terhadap Pembelajaran Daring Pada Anak Usia 5-6 Tahun Di Kecamatan Limapuluh Kota Pekanbaru. Jurnal Review Pendidikan Dan Pengajaran, 3(2). https://doi.org/10.31004/jrpp.v3i2.1222 Britto, P. R. (2012). School Readiness: A Conceptual Framework. United Nations Children’s Fund (UNICEF). Ekyana, L., Fauziddin, M., Arifiyanti, N., Pendidikan, J., & Dini, U. (2021). Parents’ Perception: Early Childhood Social Behaviour During Physical Distancing in the Covid-19 Pandemic. Jurnal Pendidikan Usia Dini, 15(2), 258–280. https://doi.org/10.21009/JPUD.152.04 Fridani, L. (2014). School readiness and transition to primary school: A study of teachers, parents and educational policy makers’ perspectives and practices in the capital city of Indonesia. In Faculty of Education, Monash University, Australia. Jalal, M. (2020). Kesiapan Guru Menghadapi Pembelajaran Jarak Jauh Di Masa Covid-19. Smart Kids: Jurnal Pendidikan Islam Anak Usia Dini, 2(1). https://doi.org/10.30631/smartkids.v2i1.61 Kokkalia, G., Drigas, A., Economou, A., & Roussos, P. (2019). School readiness from kindergarten to primary school. International Journal of Emerging Technologies in Learning, 14(11). https://doi.org/10.3991/IJET.V14I11.10090 Lutfiah, S. Z. (2020). Persepsi Orang Tua Mengenai Pembelajaran Online di Rumah Selama Pandemi Covid-19. Dealektik, 2(2). Majzub, R. M., & Rashid, A. A. (2012). School Readiness Among Preschool Children. Procedia - Social and Behavioral Sciences, 46. https://doi.org/10.1016/j.sbspro.2012.06.098 Nurdin, N., & Anhusadar, L. (2020). Efektivitas Pembelajaran Online Pendidik PAUD di Tengah Pandemi Covid 19. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(1). https://doi.org/10.31004/obsesi.v5i1.699 Nurhayati, W. (2019). Pengembangan Instrumen Kesiapan Bersekolah dan Pemetaan Kesiapan Bersekolah pada Anak Usia Dini di Indonesia. Indonesian Journal of Educational Assesment, 1(1). https://doi.org/10.26499/ijea.v1i1.4 Nurkolis, N., & Muhdi, M. (2020). Keefektivan Kebijakan E-Learning berbasis Sosial Media pada PAUD di Masa Pandemi Covid-19. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1). https://doi.org/10.31004/obsesi.v5i1.535 Pan, Q., Trang, K. T., Love, H. R., & Templin, J. (2019). School Readiness Profiles and Growth in Academic Achievement. Frontiers in Education, 4. https://doi.org/10.3389/feduc.2019.00127 Pangestuti, R., Agustiani, H., Cahyadi, S., & Kadiyono, A. L. (2018). Indonesian children ‘s readiness for elementary school: A preliminary study to the holistic approach to school readiness. Pedagogika, 132(4). https://doi.org/10.15823/p.2018.132.6 Ricciardi, C., Manfra, L., Hartman, S., Bleiker, C., Dineheart, L., & Winsler, A. (2021). School readiness skills at age four predict academic achievement through 5th grade. Early Childhood Research Quarterly, 57. https://doi.org/10.1016/j.ecresq.2021.05.006 Saodi, S., Herlina, H., & Irfan, M. (2021). The Effectiveness of Children’s Learning Time in Online Learning System During the Covid 19 Pandemic in Kindergartens. Journal of Educational Science and Technology (EST), 7(2), 148. https://doi.org/10.26858/est.v7i2.19538 Satrianingrum, A. P., & Prasetyo, I. (2020). Persepsi Guru Dampak Pandemi Covid-19 terhadap Pelaksanaan Pembelajaran Daring di PAUD. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1). https://doi.org/10.31004/obsesi.v5i1.574 Sibagariang, P. P., & S. Pandia, W. S. (2021). Teaching Approach and Teacher Self-Efficacy during Early Childhood Distance Learning. JPUD - Jurnal Pendidikan Usia Dini, 15(1), 41–59. https://doi.org/10.21009/jpud.151.03 Sit, M., & Assingkily, M. S. (2020). Persepsi Guru tentang Social Distancing pada Pendidikan AUD Era New Normal. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(2). https://doi.org/10.31004/obsesi.v5i2.756 Snow, K. L. (2006). Measuring school readiness: Conceptual and practical considerations. In Early Education and Development (Vol. 17, Issue 1). https://doi.org/10.1207/s15566935eed1701_2 Wijaya, C., Anwar Dalimunthe, R., & Muslim. (2021). Parents’ Perspective On The Online Learning In Al-Azhar Kindergarden Model Medan. JPUD - Jurnal Pendidikan Usia Dini, 15(2), 300–318. https://doi.org/10.21009/jpud.152.06 Wijayanti, R. M., & Fauziah, P. Y. (2020). Perspektif dan Peran Orangtua dalam Program PJJ Masa Pandemi Covid-19 di PAUD. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 5(2). https://doi.org/10.31004/obsesi.v5i2.768 Wulandari, H., Purwanta, E., Anak, P., Dini, U., Yogyakarta, U. N., & Biasa, P. L. (2021). Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini Pencapaian Perkembangan Anak Usia Dini di TK selama Pembelajaran Daring saat Pandemi Covid-19. Jurnal Pendidikan Anak Usia Dini, 5(1).